A Survey of Patients\' Length of Stay and Its Effective Predictors in Emergency Departments of TUMS Selected Hospitals - Hamed Basir Ghafouri; Mohammad Hosseini Kasnavieh; Marziye Alsadate Sharifi; Milad Amini; Amirreza Darzi Ramandi (Tehran University of Medical Sciences, 2017)
Background and Aim: Hospitals should be able to satisfy their clients' needs in less time and with best quality possible. Length of Stay (LOS) in hospitals is considered as a key performance indicator, especially in emergency departments. In this study, the analysis of LOS in emergency departments was performed so that some of the factors affecting patients' length of stay could be found.  Materials and Methods: This descriptive-analytical and cross-sectional study was performed in the emergency departments of two teaching hospitals of Tehran University of Medical Sciences (TUMS). Seventy-two patient samples were included. The patients' length of stay in emergency ward was measured from the entrance time until the time they left the emergency department. Data on both descriptive (mean and standard deviation) and analytical statistics (one-way ANOVA, independent sample t-test and linear regression) were analyzed with SPSS software. Results: Patients' average LOS in emergency departments was estimated at around 3 hours and 13 minutes (SD=1.52). Such variables as patients' marital status, days of the week (holidays or regular days) and admission time (day or night) were determined as the factors affecting LOS.  Conclusion: The time spent to give services in hospital emergency rooms is at an appropriate level and items such as marital status, holidays of a week, and time of the day can be referred to as factors affecting patients' length of stay. With regard to these findings, health managers can rely on the results for the effective planning and management of hospital emergency departments.